Windows PowerShell 2 for dummies - Seguis, Steve; Safari eBooks (Indianapolis, Ind. : Wiley Pub., 2009)
"Windows PowerShell 2 is the scripting language that enables automation within the Windows operating system. Packed with powerful new features, this latest version is complex, and Windows PowerShell 2 For Dummies is the perfect guide to help system administrators get up to speed. Written by a Microsoft MVP with direct access to the program managers and developers, this book covers every new feature of Windows PowerShell 2 in a friendly, easy-to-follow format"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Windows PowerShell (Computer program language); Command languages (Computer science); Scripting languages (Computer science); Systems programming (Computer science); Electronic books